Generation of highly damaging H2O+ radicals by inner valence shell ionization of water - Vendrell, Oriol; Stoychev, Spas Dimitrov; Cederbaum, Lorenz S. (ChemPhysChem, 2010)
Bye bye friend: Water molecules surround all biological structures. Inner-valence ionization of water, followed by intermolecular Coulombic decay, generates two water radical cations in close proximity. The two fragments strongly repel each other and quickly separate, gaining a large amount of translational and rotational energy (see graphic).
Im Titel erscheint bei der chemischen Formal die Ziffer 2 tiefgestellt und und das + hochgestellt
Gesehen am 31.08.2023